Destined to Leave Hindustan for Suriname? : Explaining the Motivation Behind Repatriation and Settlement of Hindustani Labour Migrants in Suriname, 1873-1940 - Kraijo, Matthijs (TSEG - The Low Countries Journal of Social and Economic History, 2022)
This article investigates the post-indenture choice of Hindustani indentured labour migrants in Suriname either to settle in Suriname or repatriate to India between 1873 and 1940. Based on extensive demographic statistical analyses and the autobiography of Rahman Mohammed Khan, this research concludes that familial relations, especially those formed in Suriname, had a strong effect on the relative share of Hindustanis settling themselves in Suriname after their contract period. Additionally, this study convincingly proves that the Surinamese context had an important effect on the development of the individual life courses of Hindustanis.